2009
DOI: 10.1051/0004-6361/200811115
|View full text |Cite
|
Sign up to set email alerts
|

Shocks in dense clouds

Abstract: Context. Observations of SiO line emission in shocks in star-forming regions indicate that silicate dust destruction must be occurring in these dense regions. Current models rely on predictions for dust destruction by sputtering in C-type shock waves. However, J-type shocks may also be relevant for interpreting the widely-observed optical line emission from species such as O I and Fe II. Aims. In this work we explore, for the first time, dust destruction in J-type shocks slower than 50 km s −1 . Methods. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 24 publications
11
112
0
2
Order By: Relevance
“…Guillet et al 2009Guillet et al , 2011. Anderl et al (2013) have shown that including them does not significantly alter the predicted OH emission of C-type models with n H of the order of 10 5 cm −3 (see their Fig.…”
Section: Scenario 1: One Outflow Two Shock Layersmentioning
confidence: 98%
“…Guillet et al 2009Guillet et al , 2011. Anderl et al (2013) have shown that including them does not significantly alter the predicted OH emission of C-type models with n H of the order of 10 5 cm −3 (see their Fig.…”
Section: Scenario 1: One Outflow Two Shock Layersmentioning
confidence: 98%
“…If confirmed as characteristic of massive star formation processes, such a high ratio could be accounted for by considering grain-grain interactions within the shock layer. Such interactions have been described as important at high pre-shock densities, and their feedback effects on both the chemical and dynamical structure of shocks have been studied by Guillet et al (2007Guillet et al ( , 2009Guillet et al ( , 2011. Unfortunately, those authors could not generate any selfconsistent solution for the pre-shock densities at work here, namely for n H = 10 6 cm −3 .…”
Section: Slab-lvg Analysismentioning
confidence: 99%
“…The gas-phase abundance of these species is strongly depleted in the ISM with respect to solar abundances because their atoms are locked onto dust grains (Savage & Sembach 1996). When dust grains evaporate in the launching region or are sputtered in shocks along the jet, these species are released into the gas-phase (Jones et al 1994;Jones 2000;May et al 2000;Draine 2004;Guillet et al 2009Guillet et al , 2011. Gas phase depletion of refractory elements has been observed by Nisini et al (2005) and Podio et al (2006Podio et al ( , 2009Podio et al ( , 2011 in HH jets from Class I sources at large distances from their driving source.…”
Section: Dust Contentmentioning
confidence: 99%